2021
DOI: 10.25130/tjes.29.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Preparation on the Corrosion Behavior of Mild Steel

Abstract: Surface preparation of engineering materials is necessary for preventing corrosion and subsequent failure of materials in service. There are different methods of surface preparations that can affect engineering materials in different ways. This study investigated the effect of surface preparation on the corrosion behavior of zinc sprayed and unsprayed mild steel. Quantitative analysis and potentiodynamic polarization techniques were used to evaluate the immersed samples of different surface preparations. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Multiple studies have demonstrated that dense oxide films on metal and alloy surfaces protect the substrates from corrosive environments with their effectiveness depending on higher surface roughness. Wasiu et al [2] discussed how differences between experimental and analytical data can rarely influence corrosion behavior due to various interacting factors. The main category influencing the electrochemical or mechanical behavior of the coated surface was found according to substrate surface conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that dense oxide films on metal and alloy surfaces protect the substrates from corrosive environments with their effectiveness depending on higher surface roughness. Wasiu et al [2] discussed how differences between experimental and analytical data can rarely influence corrosion behavior due to various interacting factors. The main category influencing the electrochemical or mechanical behavior of the coated surface was found according to substrate surface conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this, most thermal processes are designed using thermal safety distance in term of temperature and pressure, however, the limitation of this process is that the heat exchanger capacity will not be fully utilized. Corrosion is a major problem face in chemical processes involving fluids, hence, ways to reduce or eradicate it [20] [21] are; proper selection of materials (the use of corrosion resistive materials such as stainless steel), corrosion resistive alloy and non-ferrous metals [22], corrosion inhibitor-substances that reduce the rate of corrosions by forming protective layer or altering electrochemical reaction causing corrosion, cathodic protection via controlling electrochemical reaction [23] [24], surface preparation with protective coating [25], protective coatings and linings (such as paint, epoxies and polymers) to serve as a barrier for to corrosive substances, monitoring and inspecting materials for possible corrosion attack in other to apply adequate maintenance measures [26], and other corrosion measures such as testing, corrosion management programs, corrosion education and training [27].…”
Section: Introductionmentioning
confidence: 99%